(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This study examines the effectiveness of sterilization methods used for the in vitro propagation of mulberry (Morus spp.) varieties. The research was conducted at the laboratory of the “Ipak ko‘chat klaster” farm, located in the Marhamat district of the Andijan region. Bud explants from “Marhamat 2017”, “Balxi”, “Marvarid”, and “Shohtut” varieties were treated with 5% sodium hypochlorite (NaOCl) solution for 5, 7, and 10 minutes. For each variety, the number of uncontaminated explants, shoot tip condition, and viability were evaluated. The results showed that 7 minutes of sterilization provided the most favorable outcome. In addition, strict safety measures were followed to protect human health. The findings may contribute to the development of effective tissue culture protocols for mulberry propagation.